Efektivitas Penerapan Pendekatan Konstruktivis Dalam Pembelajaran Matematika - Rizky Ramadhana (GENIUS: Jurnal Inovasi Pendidikan dan Pembelajaran, 2025)
Mathematics is one of the subjects that is considered difficult for students, therefore it is not uncommon to find that the average mathematics learning outcomes of students are still below the minimum completion criteria, this also occurs at MTs Ihya Ulumiddin where the average mathematics learning outcomes of students are still below the minimum completion criteria, based on the results of observations in class, mathematics learning still uses conventional methods so that methods or approaches are needed that can improve student learning outcomes, one of which is the constructivist approach. This research is pre-experimental research with a one group pretest - posttest. The population in this study were all 47 class VII students of Mts Ihya Ulumiddin who were divided into two classes. The class used as the research sample was class VIIA with the sampling technique used was cluster random sampling. The results of the descriptive analysis show that student learning outcomes after applying the constructivist approach are categorized as high with an average of 77.26 and before the constructivist approach is applied, student learning outcomes are categorized as low with an average of 33.37. The results of this analysis provide an illustration that mathematics learning outcomes have experienced a significant increase from pretest to posttest with a gain value > 0.7. The average percentage of student responses was in the positive category. The average percentage of student activity in the good category. From the results of this research, it was concluded that the application of a constructivist approach was effective in improving students' mathematics learning outcomes.